Volume 1: Offshore Technology 2017
DOI: 10.1115/omae2017-61483
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Subsea Pipeline Routes in Shallow Waters

Abstract: This paper presents recent advances regarding a computational tool, based in Evolutionary Algorithms, for the synthesis and optimization of submarine pipeline routes. Previous works by the authors have focused on some specific issues related to the development of this tool, including the incorporation of engineering criteria such as on-bottom stability (OBS), VIV-induced fatigue in free-spanning pipelines, and flow assurance. Now, this work studies the influence of different OBS criteria for particular scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lucena et al [23] used the genetic algorithm to design subsea pipe routes, considering the seabed terrain, obstacles, and stability with the minimum pipeline length. Baioco et al [24] set the minimum pipe length and the maximum oil production as a multi-objective function and optimized the pipe route, considering the seabed terrain and the pipeline stability. Kang et al [25] proposed a method for the automatic obstacle avoidance of the pipeline route and applied the Laplacian smoothing algorithm to smooth the routes.…”
Section: Introductionmentioning
confidence: 99%
“…Lucena et al [23] used the genetic algorithm to design subsea pipe routes, considering the seabed terrain, obstacles, and stability with the minimum pipeline length. Baioco et al [24] set the minimum pipe length and the maximum oil production as a multi-objective function and optimized the pipe route, considering the seabed terrain and the pipeline stability. Kang et al [25] proposed a method for the automatic obstacle avoidance of the pipeline route and applied the Laplacian smoothing algorithm to smooth the routes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, de Lucena et al 7 applied genetic algorithms (GA) to improve their analysis for offshore scenarios. In turn, Rocha et al 8 reported how the optimization of a submarine pipeline route had been enhanced by means of a GA. Later, Baioco et al 9 successfully focused on multiobjective optimization of subsea pipeline routes in shallow waters.…”
Section: Introductionmentioning
confidence: 99%